The Role of Sorbitol in Enhancing the Performance of Whey Chia Seed-Based Edible Films: A Physical and Microscopic Evaluation - Fahrullah, Fahrullah; Fiarani, Mesil; Kisworo, Djoko; Bulkaini, Bulkaini; Septian, I Gede Nano (Faculty of Agriculture, Tompotika Luwuk University, 2025)
Edible film is a thin, edible film used as a food coating. The advantages of edible film include its biodegradability and its ability to maintain the quality and shelf life of the food product it covers. The objective of this study was to ascertain the impact of varying concentrations of sorbitol on the thickness, water vapor transmission rate, and microstructure of whey-chia seed edible film. The present study employed a Completely Randomized Design, comprising three distinct treatments, each with three replicates. The data obtained were analysed using Analysis of Variance, and if there were significant differences between treatments, these were followed by Duncan Multiple Range Test. The treatments incorporated the following: P1 (10% sorbitol), P2 (20% sorbitol), and P3 (30% sorbitol). The variables measured in this study were thickness, water vapor transmission rate and edible film microstructure. The findings demonstrated that the incorporation of sorbitol at varying concentrations elicited a highly significant effect (P<0.01) on the thickness of the edible film. However, the water vapor transmission rate test did not yield a significant difference (P>0.05). The mean thickness of the samples ranged from 0.0296 to 0.0303 mm, and the water vapor transmission rate ranged from 4.60 to 5.68 g/mm²/day. Microstructure analysis revealed that the incorporation of sorbitol enhanced the flexibility and uniformity of the distribution of the films at concentrations of 10% and 20%. However, at a concentration of 30%, the films exhibited increased rigidity and reduced flexibility. The utilization of a 20% sorbitol concentration was identified as the optimal treatment.